2020
DOI: 10.1016/j.molmet.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of iRhom2 protects against diet-induced obesity by increasing thermogenesis

Abstract: ObjectiveObesity is the result of positive energy balance. It can be caused by excessive energy consumption but also by decreased energy dissipation, which occurs under several conditions including when the development or activation of brown adipose tissue (BAT) is impaired. Here we evaluated whether iRhom2, the essential cofactor for the Tumour Necrosis Factor (TNF) sheddase ADAM17/TACE, plays a role in the pathophysiology of metabolic syndrome.MethodsWe challenged WT versus iRhom2 KO mice to positive energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 91 publications
(125 reference statements)
0
25
0
Order By: Relevance
“…Adipose macrophages in obesity are associated with the production of pro-inflammatory adipokines; for instance, known ADAM17 targets, IL-6R and TNF-⍺ (Minxuan et al, 2019, Xu et al, 2020. Although two studies were contradictory in their findings, possibly as they used differently derived Rhbdf2 -/mouse models, a role for iRhom2 in modulating adipose inflammation, metabolism and obesity is proposed (Badenes et al, 2020, Skurski et al, 2020. J o u r n a l P r e -p r o o f iRhom2 may participate in the cellular response to viruses iRhom2 was recently proposed as a mediator of the antiviral response via its regulation of stimulator of interferon genes (STING) in human monocytic THP-1 cells and murine bonemarrow-derived macrophages (Luo et al, 2016).…”
Section: Irhom2: Oesophageal Cancer and Inflammatory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Adipose macrophages in obesity are associated with the production of pro-inflammatory adipokines; for instance, known ADAM17 targets, IL-6R and TNF-⍺ (Minxuan et al, 2019, Xu et al, 2020. Although two studies were contradictory in their findings, possibly as they used differently derived Rhbdf2 -/mouse models, a role for iRhom2 in modulating adipose inflammation, metabolism and obesity is proposed (Badenes et al, 2020, Skurski et al, 2020. J o u r n a l P r e -p r o o f iRhom2 may participate in the cellular response to viruses iRhom2 was recently proposed as a mediator of the antiviral response via its regulation of stimulator of interferon genes (STING) in human monocytic THP-1 cells and murine bonemarrow-derived macrophages (Luo et al, 2016).…”
Section: Irhom2: Oesophageal Cancer and Inflammatory Diseasementioning
confidence: 99%
“…Adipose macrophages in obesity are associated with the production of pro-inflammatory adipokines; for instance, known ADAM17 targets, IL-6R and TNF-⍺ ( Minxuan et al, 2019 , Xu et al, 2020 ). Although two studies were contradictory in their findings, possibly as they used differently derived Rhbdf2 -/- mouse models, a role for iRhom2 in modulating adipose inflammation, metabolism and obesity is proposed ( Badenes et al, 2020 , Skurski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…To maintain energy homeostasis, the AT responds to cues from multiple organs/systems, such as the immune system and the gut. Colin Adrain (IGC) showed that the pseudoprotease Rhomboid family member 2 not only has a role in immunity, but also mediates AT physiology, acting as a negative thermogenic regulator of brown AT (BAT) and inhibiting white AT (WAT) browning (development of beige adipocytes within the WAT) during obesity, possibly due to its regulation of ADAM metallopeptidase domain 17 (or tumor necrosis factor-a-converting enzyme) activity [5]. Rub en Cereijo (Francesc Villaroya's Lab, University of Barcelona, Spain) talked about a new batokine (cytokine secreted by the BAT), named chemokine (C-X-C motif) ligand 14, which recruits M2 macrophages to the BAT, promoting thermogenesis, browning of the WAT and improving glucose homeostasis [6].…”
Section: Immunometabolic Regulation Of Energy Balancementioning
confidence: 99%
“…Loss of iRhom2 has been shown to prevent the release of TNF following lipopolysaccharide stimulation, mediated through the loss of ADAM17 activity [11]. Recent studies have shown contradicting results regarding the effect of global iRhom2 deletion on metabolic inflammation following HFD [12,13]. Badenes et al showed that deletion of iRhom2 protected against HFDinduced obesity through increased thermogenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown contradicting results regarding the effect of global iRhom2 deletion on metabolic inflammation following HFD [12,13]. Badenes et al showed that deletion of iRhom2 protected against HFDinduced obesity through increased thermogenesis [13]. However, another study showed that global loss of iRhom2 resulted in increased fat gain as well as increased metabolic inflammation following HFD [12].…”
Section: Introductionmentioning
confidence: 99%